2005
DOI: 10.1096/fj.04-2915fje
|View full text |Cite
|
Sign up to set email alerts
|

Green tea extract and (−)‐epigallocatechin‐3‐gallate, the major tea catechin, exert oxidant but lack antioxidant activities

Abstract: Green tea is the most widely consumed beverage. It has attained high reputation as a health-promoting dietary component ascribed to the antioxidant activity of (-)-epigallocatechin-3-gallate (EGCG), its main polyphenolic constituent. Evidence is increasing that tea constituents can be cell damaging and pro-oxidant themselves. These effects were suggested to be due to spontaneous H2O2 generation by polyphenols in solution. In the present study, we investigated the oxidant and antioxidant properties of green tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
172
1
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(199 citation statements)
references
References 63 publications
18
172
1
3
Order By: Relevance
“…In the case of EGCG, there may be unidentified specific cell surface receptors for EGCG that are involved in generation of ROS. However, another possibility is that EGCG may directly generate ROS (including H 2 O 2 ) in a receptor-independent fashion either by autoxidation (64) or by acting as a pro-oxidant in vivo at physiological pH (65). Thus, despite many claims that EGCG is an antioxidant in vitro (66), beneficial bioactivity of EGCG may in fact depend on its ability to behave as a pro-oxidant in physiological contexts that initiates acute intracellular signaling events such as those described in the present study.…”
Section: Exploring Potential Mediators Of Vascular Actions Of Egcg Upmentioning
confidence: 99%
“…In the case of EGCG, there may be unidentified specific cell surface receptors for EGCG that are involved in generation of ROS. However, another possibility is that EGCG may directly generate ROS (including H 2 O 2 ) in a receptor-independent fashion either by autoxidation (64) or by acting as a pro-oxidant in vivo at physiological pH (65). Thus, despite many claims that EGCG is an antioxidant in vitro (66), beneficial bioactivity of EGCG may in fact depend on its ability to behave as a pro-oxidant in physiological contexts that initiates acute intracellular signaling events such as those described in the present study.…”
Section: Exploring Potential Mediators Of Vascular Actions Of Egcg Upmentioning
confidence: 99%
“…High dosages of EGCG can induce DNA damage [41,103,124] due to the generation of hydrogen peroxide. A recent study showed that EGCG neither directly scavenges hydrogen peroxide nor mediates other antioxidant activities, but instead increases hydrogen-peroxide-induced oxidative stress and DNA damage in vitro [19]. EGCG causes oxidative damage to isolated and cellular DNA [23].…”
Section: Possible Prooxidant Activity and Carcinogenicity Of Some Polmentioning
confidence: 99%
“…Detection of intracellular ROS was performed as previously described [9]. Briefly, cells were incubated with 50 lM 2',7'-dichlorodihydrofluorescein diacetate (DHCF-DA) (Molecular Probes, Eugene, OR, USA) (dissolved in dimethyl sulfoxide) for 30 min at 37°C followed by treatment with trans-resveratrol.…”
Section: Measurements Of Ros Levels and Oxidative Damagesmentioning
confidence: 99%
“…Previous studies have indicated that some nutraceuticals exhibit potent anti-tumor properties and can modulate apoptosis, differentiation and cell cycle, probably by virtue of their anti-oxidant functions. However, in vitro experiments reported that most of them behave as potent pro-oxidants molecules [6,9,40]. For example, organosulfur molecules from garlic, such as the oil-soluble diallyl disulfide [12,13], diallyl trisulfide [22], or the water-soluble S-allylmercaptocysteine [63] have been demonstrated to induce growth arrest and apoptosis dose-dependently by increasing ROS production.…”
Section: Introductionmentioning
confidence: 99%